Treatment of public policies on information and technology in Colombian scientific journals of information science - Camperos-Reyes, Jacquelin Teresa [UNESP]; Sant'Ana, Ricardo César Gonçalves [UNESP]; De Carvalho, Ângela Maria Grossi [UNESP] (Universidad de Antioquia, 2018)
This paper proposes an approximation between the Information Science and the Public Policies of Information and Technology. The objective is to identify the treatment that the Public Policies of Information and Technology have received, through the study of the elements of content addressed in the scientific publications of the Colombian Information Science area. The content elements were approached in order to study the direction that the theme has received in these publications in the context of the Information Society. The SciELO system was used, referring to the subject Applied Social Sciences in Colombia, having selected two journals of the field of Information Science: Revista Interamericana de Bibliotecología and Signo y Pensamiento, analyzing the period between 2000-2016. It is considered that the discussions have been few and mostly focused on some topics of Information Science, without finding analyzes integrated with the proposals of the government, in the topics considered by them as fundamental in the Information Society. Within the analyzed scientific publications, there is a wide discussion about the role of public libraries as important agents for the development of the Information Society. It is concluded that new directions are needed to deepen relations between Information Society and scientific and technological development, information society and public information policies, including historical and epistemological foundations of public information policies.
Tratamento das políticas públicas de informação e tecnologia em periódicos científicos colombianos da ciência da informação
Keywords: Colombian scientific journals; Information and technology public policies; Information science; Information society